Prolonged refrigeration does not alter isoprostanes concentration in human milk. (12th December 2022) - Peila, Chiara; Longini, Mariangela; Toni, Anna Laura; Sottemano, Stefano; Bertino, Enrico; Buonocore, Giuseppe; Coscia, Alessandra
Abstract: Background: The Academy of Breastfeeding Medicine published a clinical protocol for Human Milk storage, recommending refrigeration at a temperature of 4 °C up to 4 d as the optimal conditions for the safety and bactericidal capacity of Human Milk. However, few studies were conducted to evaluate the change in milk composition during this type of refrigeration storage. Aim: To elucidate some uncertainties regarding the Human Milk composition and prolonged cold storage, we have investigated the effects of storage at 4 °C up to 96 h on an important category of oxidative stress markers: the Isoprostanes (F2-isoprostanes, F4-neuroprostanes and F3-isoprostanes). Material and method: The experiment was repeated 3 times to ensure reproducibility of the results. We enrolled 3 donating healthy mothers for each time (total: 9 mothers). Milk was collected with standard extraction methods. Immediately after collection, each Human Milk sample from each mother was pooled and then divided into 5 aliquots. One aliquot (0 h) was immediately frozen at −80 °C until the analysis. The other aliquots (24 h, 48 h, 72 h, 96 h) were stored in a refrigerator at 4 °C respectively for 24, 48, 72 and 96 h, then immediately frozen at −80 °C until the analysis. Milk samples were then used to determine concentration of Isoprostanes in Liquid Chromatography - Mass Spectrometry and Liquid Chromatography - Tandem Mass Spectrometry. Results: Isoprostanes were detectable in all Human Milk samples. There was no significant trend of the concentration of the tested analytes over time. Discussion and conclusion: This study provides evidence of the presence in human milk of all the tested isoprostanes: in particular, F2-isoprostanes, F4-neuroprostanes and F3-isoprostanes. Refrigeration and storage of fresh Human Milk in controlled conditions for 96 h did not significantly affect its bioactivity and nutritional quality related with these biomarkers.